Development and field tryout of games in high school geometry - Carnaje, Norma Luz E. (1976)
The purpose of the study was to design games pertaining to some topics in high school geometry as reinforcement to what students learned. Two high school geometry books were reviewed and from which selected topics were used as bases for the development of the games. The topics chosen were: common sense and exact reasoning, polygonal regions and their area, lines, planes and separation, and plane coordination. The satisfying results of the students' responses showed that the games developed are suitable for third year high school geometry students. All the games met the 2.80 criterion rating set for suitability of the game. The mean rating was affected by the type of students who played the game.